Tetrahydrocannabinol and dopamine D1 receptor - Lee, Jiwon (Frontiers in Neuroscience, 2024)
Dopamine is a hormone that is released by the adrenal gland and influences motor control and motivation. Dopamine is known to have 5 receptors which are D1, D2, D3, D4 and D5, which are further categorized into 2 families: D1 family and D2 family. The D1 family is known to play a role in motivation and motor control whereas the D2 family is known to affect attention and sleep. THC, a type of cannabinoid, can lead to feelings of euphoria, anxiety, fear, distrust, or panic. THC is known to affect dopamine in regions such as the anterior cingulate cortex (ACC), and plays a role in fundamental cognitive processes. Although there is a vast amount of research between the relationship of THC on dopamine, there continues to be limited research in relation to THC on dopamine receptors. The D1 receptor plays a role in several essential functions, such as memory, attention, impulse control, regulation of renal function, and locomotion. Accordingly, this review is intended to summarize the relationship between THC and D1 receptors, highlighting key gaps in the literature and avenues for future research.